The Corsini Encyclopedia of Psychology 2010
DOI: 10.1002/9780470479216.corpsy0152
|View full text |Cite
|
Sign up to set email alerts
|

California Psychological Inventory

Abstract: The California Psychological Inventory (CPI) is a self‐report, paper and pencil test comprised of 434 True‐False items. There is also a 260‐item short form. Questions relate to a person's typical behaviors, opinions, feelings, and attitudes regarding family, ethical, and social matters. It can be administered to individuals between the ages of 12 and 70 having a minimum of a fourth grade education. Results of the test are presented as a profile comprised of 20 scales, 3 vectors (or factors), and a variety of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…In this first long-term follow-up, breath holding duration showed to be a reliable measure over time and its high test-retest reliability suggests the determination of BHT by relatively stable trait characteristics comparable to common personality inventories with 1-year follow-up retests (Groth-Marnat and Mullard, 2010) or other peripheral physiological trait measures such as heart rate variability (Bertsch et al, 2012). …”
Section: Discussionmentioning
confidence: 74%
“…In this first long-term follow-up, breath holding duration showed to be a reliable measure over time and its high test-retest reliability suggests the determination of BHT by relatively stable trait characteristics comparable to common personality inventories with 1-year follow-up retests (Groth-Marnat and Mullard, 2010) or other peripheral physiological trait measures such as heart rate variability (Bertsch et al, 2012). …”
Section: Discussionmentioning
confidence: 74%
“…Therapists commonly use the HTP with children between the ages of 3/4 to 15 years (Bluestein, 1978). Due to the familiarity of a house, a tree, and a person, children doing a freehand drawing project their feelings onto these prototypical images (Groth-Marnat, 1997). The authors also used the HTP like previous researchers to locate “common factors in an identified group of people” (Oster, & Crone, 2004, p. 92; Nuttman-Shwartz et al, 2010; Rudenberg et al, 1998; Wang, Xu, & Wang, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it may be that when provided with effective responses to risky social situations, women at risk for sexual victimization are able to execute skillfully these responses, suggesting that difficulties in responding effectively in risky situations may be specific to decoding and decision-making processes. Related work provides additional evidence suggesting that difficulties may not extend to the enactment phase (i.e., response performance) of the SIP model (e.g., Holtzworth-Munroe, 1992; Morrison et al, 1987). For example, Morrison et al (1987) indirectly tested the enactment phase of the SIP model (i.e., response performance) by comparing violent men, martially discordant non-violent men, and satisfactorily married men.…”
Section: Discussionmentioning
confidence: 99%